Genetic Polymorphism of GABRG2 rs211037 is Associated with Drug Response and Adverse Drug Reactions to Valproic Acid in Chinese Southern Children with Epilepsy - Lu J; Xia H; Li W; Shen X; Guo H; Zhang J; Fan X (Dove Medical Press, 2021)
Jieluan Lu,1 Hanbing Xia,2 Wenzhou Li,2 Xianhuan Shen,1 Huijuan Guo,2 Jianping Zhang,1 Xiaomei Fan2 1Department of Clinical Pharmacology, College of Pharmacy, Jinan University, Guangzhou, 510632, People's Republic of China; 2Department of Pharmacy, Baoan Women's and Children's Hospital, Jinan University, Shenzhen, 518102, People's Republic of ChinaCorrespondence: Jianping ZhangDepartment of Clinical Pharmacology, College of Pharmacy, Jinan University, 601 W. Huangpu Avenue, Guangzhou, 510632, People's Republic of ChinaTel +86 20 85220261Email tzhangjp@jnu.edu.cnXiaomei FanDepartment of Pharmacy, Baoan Women's and Children's Hospital, Jinan University, 56# Yulv Road, Baoan District, Shenzhen, 518102, People's Republic of ChinaTel +86 755 27863999Email xmfane@163.comBackground: Valproic acid (VPA) is recommended as a first-line treatment for children with epilepsy. GABRG2 polymorphism is found to be associated with epilepsy susceptibility and therapeutic response of anti-seizure medications (ASM); however, the role of GABRG2 in VPA treatment still remains unknown.Objective: The purpose of this study was to explore the association of GABRG2 gene polymorphism with the drug response and adverse drug reactions (ADRs) related to VPA.Methods: A retrospective study including 96 Chinese children with epilepsy treated by VPA was carried out. The ADRs were collected during VPA therapy and GABRG2 rs211037 in enrolled patients was genotyped using Sequenom MassArray system. A network pharmacological analysis involved protein-protein interaction and enrichment analysis was constructed to investigate the potential targets and pathways of GABRG2 on VPA-related ADRs.Results: Among 96 patients, 41 individuals were defined as seizure together with 49 patients with seizure-free and 6 patients unclassified. Carriers of homozygote GABRG2 rs211037 CC genotype exhibited seizure-free to VPA (P = 0.042), whereas those with CT genotype showed seizure. Furthermore, CC genotype had predisposition to digestive ADRs (P = 0.037) but was a protective factor for VPA-associated weight gain (P = 0.013). Ten key genes related to digestive ADRs and weight gain induced by VPA were identified by network pharmacological analysis and mainly involved in "GABAergic synaptic signaling", "GABA receptor signaling", and "taste transduction" pathways/processes through enrichment analysis.Conclusion: This study revealed that GABRG2 variation exerted a predictable role in the efficacy and safety of VPA treatment for Chinese children with epilepsy.Keywords: children with epilepsy, GABRG2, gene polymorphism, valproic acid, therapeutic response, adverse drug reactions